The Perceptions of Petra Christian University Male and Female Students toward the Language used in a Hotel Website and the Hotel Itself - Shelia M Abigail; Jusuf I Ibrahim (Kata Kita: Journal of Language, Literature, and Teaching, 2014)
The purpose of this study is to analyze the perceptions of the male and female students of Petra Christian University toward the language used in a three-star hotel website in Surabaya and toward the hotel itself. I want to know if the perceptions toward the language will influence the perceptions toward the hotel which writes the website. The respondents of this study are 30 male and 30 female students of Petra Christian University. Here, there are some similarities and differences found between the male and female students’ perceptions toward the language used in a three-star hotel website in Surabaya and toward the hotel itself. It seems that the female students usually see language as one important way to know the hotel. On the other hand, it seems that the male students do not really care about what kind of language that is used in a hotel website